2019
DOI: 10.2478/jomb-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Rs1799817 in INSR associates with susceptibility to polycystic ovary syndrome

Abstract: Summary Background Insulin and its receptor (INSR) have been implicated in the etiology of the polycystic ovarian syndrome (PCOS). Here, we investigate the association between INSR rs1799817 polymorphism and PCOS in Saudi Arabian women. Methods study group included 126 PCOS women and 118 normo-ovulatory matched controls. The demographic data was recorded, and the plasma levels of glucose, lipids, leptin, E2, LH, FSH, T, SHBG, and insulin were determined. The genotypic and allele frequencies of rs1799817 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Till now, PCOS pathophysiology is unclear. Specific genetic patterns that affect the formation, regulation, and actions of sex hormones and insulin receptors seem to contribute to disease progression ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Till now, PCOS pathophysiology is unclear. Specific genetic patterns that affect the formation, regulation, and actions of sex hormones and insulin receptors seem to contribute to disease progression ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the syndrome has not been clarified completely yet. Certain genetic patterns that impact for example synthesis, regulation and action of sex hormones and the insulin receptor, but also gestational factors like high maternal levels of androgens or AMH (anti-Müllerian hormone) seem to contribute to the onset of the disease [ 4 , 5 , 6 ]. Postnatal lifestyle factors like inadequate nutrition accompanied by a lack of physical exercise promote the development of the disease as they often result in obesity and disturbances of the glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported previously that DNA methylation do not participate in pre-ovulatory down-regulation of HSD3B1, CYP19A1 and CYP11A1 in the follicle of bovine but it could significantly play role in permanent silencing of gene CYP19A1 in the large granuloosa lutein cells . Previously insulin and INSR have been linked in the etiology of the (PCOS) polycystic ovarian syndrome (Daghestani, 2020). However, DNA methylation analysis demonstrated that methylation of the gene of the INSR gene was linked with insulin resistance of PCOS (Zhong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%